Fathering Japan: Japan's Strategy for Achieving Gender Equality in Response to UN Criticism - Rudiono Rudiono; Havidz Ageng Prakoso (Universitas Muhammadiyah Malang, 2022)
This journal aims to explain Japan's strategy in achieving gender equality in response to UN criticism through the Ikumen Project/ NPO Fathering Japan. The condition of gender inequality in Japanese society has generated worldwide attention and has also received criticism from the United Nations (UN) through CEDAW (The Convention on the Elimination of All Forms of Discrimination against Women). This is due to the high application of conventional cultural values ​​of Japanese society which is commonly referred to as patriarchal culture. Therefore, the theory and concept used in this research is Gender Empowerment which looks at the efforts of state actors through the government in empowering men and women, Civil Society by looking at the important role of civil society groups in dealing with content trends in an organization. Countries and the concept of the Non-Profit Organization which looks at the history of the involvement of NPOs in dealing with several problems in the country. The author uses qualitative research and descriptive research by collecting data from secondary sources, books, theses and theses, journals and articles from online sources. The results of the study show that the increased participation of men in child care in 2017. This is the result of the existence of cooperation between the Japanese government and NPO Fathering Japan as an effort to increase public awareness to shift conventional cultural values, namely patriarchy which has become the main cause gender inequality to get criticism and pressure from several UN panels to immediately address the related issues and towards the achievement of gender equality.